Place Matters: Geographic Distribution of Abortion Fund Services - Erin R. Johnson; Monica R. McLemore (Health Equity)
Background: Where you live impacts your access to all forms of health care, but abortion in particular. In response to restrictions on abortion, communities have organized to support those seeking abortion care via abortion funds. This study documents the services provided by these organizations and examines how they have been shaped by local conditions. Methods: Data come from a content analysis of the websites of all abortion funds affiliated with the National Network of Abortion Funds and interviews with 22 abortion fund leaders. Content analysis data presented include data about abortion funds’ catchment area and what services funds provide. Results: Types of support offered by abortion funds include procedure funding, practical support, emotional support, other sexual health services, and parenting support. Interviews with fund leaders show that these services are shaped by local policies, cultural and geographic specifics of their catchment area, local clinics, and ties to other organizations in funds’ communities. Discussion: Abortion funds are a diverse group of organizations that provide a variety of services to help patients overcome barriers to abortion. The geographic patterning of their services suggest that funds are responding to local environments, with the greatest variety of services being offered by funds in the South. Health Equity Implications: Abortion funds’ service offerings clearly respond to the barriers to abortion described in the literature, driven by the needs of their local communities. This is particularly relevant in a post-Dobbs environment, as patients in some parts of the country find abortion even farther out of their reach.